Listen well to score better / Aiza Johari, Norseha Unin and Ch’ng Looi Chin - Johari, Aiza; Unin, Norseha; Ch’ng, Looi Chin (Universiti Teknologi MARA Cawangan Kedah, 2017)
Many language students face difficulties when listening to a second language. For English as a Second Language (ESL) students, listening is not usually a significant part of their lessons. Educators usually pay more attention to reading, writing and speaking skills, resulting in listening anxiety among students. Additionally, listening activities are often carried out only to test the students’ abilities, which may also lead to anxiety and apprehension (Vandergrift, 1999). According to Young (1992), anxiety is one of the key elements for poor listening abilities. Effective listening requires students to apply certain mental steps to address their listening anxiety or challenges. Goh (2000) stated that teaching listening strategies to the students is very helpful for developing students’ comprehension. In this study, 100 participants were selected to examine the influence of metacognitive awareness strategies on their listening comprehension. The study was conducted in two stages of Pre-test and Post-test for MCQ (listening comprehension) and Metacognitive Awareness Listening Questionnaire (MALQ), adopted from Vandergrift et al. (2006). In general, based on the MCQ scores, the findings showed an increase in the percentage of correct answers. As such, the metacognitive strategy awareness has positively influenced the test scores. Future studies are recommended to explore how metacognitive strategies can impact the students’ listening performance